2012
DOI: 10.1128/ec.00237-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of CBS 2479, the Standard Type Strain of Trichosporon asahii

Abstract: bTrichosporon asahii is one of the important opportunistic pathogenic fungi. Here, we first report the draft nuclear chromosome genome sequence and mitochondrial genome sequence of T. asahii CBS 2479, which is a standard strain of T. asahii that was isolated from a progressive psoriatic lesion. COG analysis predicted that 3,131 genes were assigned to 23 functional categories and that 628 genes were predicted to have a general function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Libraries were Nextera® DNA Library Preparation Kit and sequencing using a 2 × 150 nucleotide paired‐end strategy. Library adaptators of paired‐ends read were trimmed with Cutadapt version 1.18 (https://doi.org/10.14806/ej.17.1.200) and then mapped to the 78 scaffolds of the reference genome of CBS2479 23 (GenBank accession number ) using the Burrows‐Wheeler Alignment tool, BWA version 0.7.13 29 with the BWA‐mem algorithm. SAMtools version 1.9 and Picard tools version 1.94 (http://broadinstitute.github.io/picard) were then used to filter, sort, convert SAM files and assign read groups and mark duplicate reads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Libraries were Nextera® DNA Library Preparation Kit and sequencing using a 2 × 150 nucleotide paired‐end strategy. Library adaptators of paired‐ends read were trimmed with Cutadapt version 1.18 (https://doi.org/10.14806/ej.17.1.200) and then mapped to the 78 scaffolds of the reference genome of CBS2479 23 (GenBank accession number ) using the Burrows‐Wheeler Alignment tool, BWA version 0.7.13 29 with the BWA‐mem algorithm. SAMtools version 1.9 and Picard tools version 1.94 (http://broadinstitute.github.io/picard) were then used to filter, sort, convert SAM files and assign read groups and mark duplicate reads.…”
Section: Methodsmentioning
confidence: 99%
“…Other haplotypes are described in Spain, Japan and Brazil 20,21 . In 2012, Yang et al sequenced the whole genome of two strains of T. asahii (an environmental isolate, CBS8904, recovered from maize cobs, in 1998, Illinois, USA 22 and a clinical isolate, CBS2479, the type strain, recovered in Japan in 1929 from a psoriasis lesion) 23 …”
Section: Introductionmentioning
confidence: 99%
“…the species option was ‘cryptococcus’). For GeneMark, the gene model was trained using data from the Trichosporon asahii CBS 2479 genome (Yang et al, ). In both cases, only complete genes coding for at least 100 amino acid residues were included.…”
Section: Methodsmentioning
confidence: 99%
“…The perfectfrombam module was run with the following parameters: min insert = 100, max insert = 500, repetitive max qual = 3, perfect min qual = 4, and perfect min alignment score = 150. For T. asahii, the published genome for strain CBS 2479 (Yang et al 2012) was used. The genome sequence data was also used in a separate study that focuses on fungal systematics (Takashima et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…We sequenced the genomes of Trichosporon coremiiforme, T. faecale, T. inkin, and T. ovoides and downloaded that of T. asahii strain CBS2479 (Supplemental Table S1; Yang et al 2012). The genome sizes of T. coremiiforme and T. ovoides (40)(41)(42) relative to those of closely related T. asahii, T. faecale, and T. inkin (20)(21)(22)(23)(24)(25) suggested that these two species experienced recent genome expansions.…”
Section: Recent and Independent Genome Hybridizations In Trichosporonmentioning
confidence: 99%